Assessing transmission blockade in Plasmodium spp. - Blagborough, A; Delves, M; Ramakrishnan, C; Lal, K; Butcher, G; Sinden, R (2013)
Here we describe a series of methods that can be used to assess the activities of "vaccines," drugs, and genetically modified vectors, for their abilities to inhibit transmission of Plasmodium from its vertebrate to its mosquito hosts. The selection of method to be used is determined by the purpose of the experiment, which can include the determination of the site/time of activity, and/or the potential reduction in transmission achieved.